Assessing information literacy among students of Quezon City Science High School - Rulloda, Venice A. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study was conducted to determine the current information literacy level among students of Quezon City Science High School and identify the factors that affect their information literacy competency. It sought to find out whether students from different year levels have the same or different information literacy competencies, identify whether their curriculum, library instruction received, and frequency of library use affect their information literacy competency.